LITERASI SAINS BERBASIS NILAI – NILAI ISLAM - Suratun (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
A society that has a civilization in science and technology that is developing rapidly, it turns out that it is not balanced with awareness in religion. The method in this study is a literature review that discusses the idea of ​​Islamic Value-Based Scientific Literacy. So that the more a person has high knowledge, the closer that person is to God and the more that person has high knowledge, the better his behavior will be because he will understand how to behave in his life well. Scientific literacy based on Islamic values ​​can also be interpreted as the ability to engage with science (science) on related issues and with scientific ideas (ideas) as a reflection as a religious citizen.